ENHANCED EXTERNAL COUNTERPULSATION REDUCES INDICES OF CENTRAL BLOOD PRESSURE AND MYOCARDIAL OXYGEN DEMAND IN PATIENTS WITH LEFT VENTRICULAR DYSFUNCTION - Beck, Darren T. (Clin Exp Pharmacol Physiol, 2015)
Enhanced external counterpulsation (EECP) therapy decreases angina episodes and improves quality of life in patients with left ventricular dysfunction (LVD). However, the underlying mechanisms relative to the benefits of EECP therapy in patients with LVD have not been fully elucidated. The purpose of this study was to investigate the effects of EECP on indices of central hemodynamics, aortic pressure wave reflection characteristics and estimates of LV load and myocardial oxygen demand in patients with LVD. Patients with chronic stable angina and left ventricular ejection fraction (LVEF) <40%, but > 30%, were randomized to either an EECP (LVEF=35.1±4.6%; n=10) or sham-EECP (LVEF=34.3±4.2%; n=7) group. Pulse wave analysis (PWA) of the central aortic pressure waveform (AoPW) and LV function were evaluated by applanation tonometry before and after 35 1-hr sessions of EECP or Sham EECP. EECP therapy was effective in reducing indices of left ventricular wasted energy (LVEw) and myocardial oxygen demand (TTI) by 25% and 19%, respectively. In addition, indices of coronary perfusion pressure (DTI) and subendocardial perfusion (SEVR) were increased by 9% and 30% after EECP, respectively. Our data indicate that EECP may be useful as adjuvant therapy for improving functional classification in heart failure patients through reductions in central blood pressure, aortic pulse pressure, wasted left ventricular energy, and myocardial oxygen demand which suggests improvements in ventricular-vascular interactions.